2016
DOI: 10.1080/21691401.2016.1261033
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of curcumin-loaded magnetic hydrogel nanocomposite (nanocurcumin) against doxorubicin-induced cardiac toxicity in rat cardiomyocyte cell lines

Abstract: Curcumin, is a yellow substance extracted from Curcuma longa rhizomes, it is a crystalline compound that has been traditionally applied in culinary practices and medicines in India. The aim of our study is to demonstrate the efficacy of curcumin-loaded magnetic hydrogel nanocomposite in the treatment of heart hypertrophy. 10 rats weighing 150-200 g each were induced with heart failure using 2.5 mg/kg doxorubicin for 2 weeks. The test groups were treated with curcumin-loaded magnetic hydrogel nanocomposite whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 36 publications
4
31
0
Order By: Relevance
“…It has been reported that the protective effect of CUR on acute DOX-induced toxicity is related to its antioxidant capacity. 33 Measurements of those biomarkers in the rat model further demonstrated the involvement of free radical over-formation and oxidative stress in DOX-induced cardiotoxicity. In contrast with the control, free DOX alone treatment caused a remarkable elevation of MDA and escalating levels of SOD and GSH-Px in rat heart tissue, which could be significantly improved by CPDMC but not the cocktail formulation at same dosages.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that the protective effect of CUR on acute DOX-induced toxicity is related to its antioxidant capacity. 33 Measurements of those biomarkers in the rat model further demonstrated the involvement of free radical over-formation and oxidative stress in DOX-induced cardiotoxicity. In contrast with the control, free DOX alone treatment caused a remarkable elevation of MDA and escalating levels of SOD and GSH-Px in rat heart tissue, which could be significantly improved by CPDMC but not the cocktail formulation at same dosages.…”
Section: Discussionmentioning
confidence: 96%
“…Rats were randomly allocated into four groups (n=30 per group): control, SFN, DOX and DOX plus SFN (DOX/SFN) groups. Rats in the DOX and DOX/SFN groups were intraperitoneally injected with DOX (TCI Chemical Industry Development Inc., Tokyo, Japan) dissolved in saline at 2.5 mg/kg body weight every other day for six times, and the accumulated dose was 15 mg/kg . SFN (Sigma‐Aldrich, St Louis, MO, USA) dissolved in 1% dimethyl sulfoxide (DMSO) and diluted in saline was subcutaneously administered at 0.5 mg/kg every day in rats in the SFN and DOX/SFN groups.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, Namdari and Eatemadi [198] demonstrated the cardioprotective effect of CUR-loaded magnetic hydrogel nanocomposite (Cur-NIPAAM-MAA-NP) against doxorubicin-induced cardiac toxicity in rats. They reported that the nanoparticles were successfully synthetized with 91% of efficiency of entrapment.…”
Section: Cardiovascular Effects Of Curcumin-loaded Nanoparticlesmentioning
confidence: 99%